Bougie‐related airway trauma: dangers of the hold‐up sign1. (March 2014) - Marson, B. A.; Anderson, E.; Wilkes, A. R.; Hodzovic, I.
Summary The bougie is a popular tool in difficult intubations. The hold‐up sign is used to confirm tracheal placement of a bougie. This study aimed to establish the potential for airway trauma when using this sign with an Eschmann re‐usable bougie or a Frova single‐use bougie. Airways were simulated using a manikin (hold‐up force) and porcine lung model (airway perforation force). Mean (SD) hold‐up force (for airway lengths over the range 25–45 cm) of 1.0 (0.4) and 5.2 (1.1) N were recorded with the Eschmann and Frova bougies, respectively (p < 0.001). The mean (SD) force required to produce airway perforation was 0.9 (0.2) N with the Eschmann bougie and 1.1 (0.3) N with the Frova bougie (p = 0.11). It is possible to apply a force at least five times greater than the force required to produce significant trauma with a Frova single‐use bougie. We recommend that the hold‐up sign should no longer be used with single‐use bougies. Clinicians should be cautious when eliciting this sign using the Eschmann re‐usable bougie.